The role of knowledge management in the decision- making processes of workers at Aqaba Container Port Company (ACT) in Jordan - Sharari, Fayiz Emad Addin Awad (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to reveal the role of knowledge management in decision- making processes among workers at Aqaba Container Port Company in Jordan، the study sample consisted of (193) males and (57) females، and among the most important findings of the study: there are statistically significant differences between Average degrees of variables (knowledge generation، knowledge storage، knowledge distribution، and application of knowledge) that were in favor of females and also here are statistically significant differences for the decision- making process that were in favor of males، and also that knowledge management is an important and necessary tool for practicing the various administrative activities in the company، and work to provide requirements and requirements for applying knowledge management in the company and in other fields، where the researcher made the following recommendations: The need for the company to adopt an objective system of material and moral incentives that rewards knowledge efforts، as well as encouraging workers to be creative and produce knowledge، and strive towards developing their knowledge capabilities.